The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1751-1097.2011.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Photosynthetic Components of Wheat Genotypes Under Rain‐fed and Irrigated Conditions

Abstract: The major environmental factor limiting the range of adaptation for wheat is drought. Fourteen wheat genotypes (Triticum aestivum L.) were grown under two environments (irrigated and rain fed) to determine physiological and photosynthetic responses to drought. Combined analysis of variance of the data showed that the environment was a significant source of variation for leaf chlorophyll content (LCC), stomatal conductance (g(s)) and grain yield (GY). Wheat genotypes differed significantly for LCC, g(s) and GY.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…An enhanced grain yield of wheat is consistently associated with changes in photosynthetic characteristics, such as P n , T r and g s of the flag leaf [ 45 ]. The magnitude of the increases in P n , T r and g s found in both our previous study by Guo et al [ 20 ] and the present study was similar to reported results concerning winter wheat from studies by Khamssi et al [ 46 ], Sun et al [ 47 ] and Zhang et al [ 48 ], reflecting the beneficial effects of SI in these photosynthetic parameters. Some studies have reported that enhancing P n and g s , particularly at the mid and later stages of grain filling, has significant effects on improving grain yield of crops, such as winter wheat, maize, rice [ 19 , 49 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…An enhanced grain yield of wheat is consistently associated with changes in photosynthetic characteristics, such as P n , T r and g s of the flag leaf [ 45 ]. The magnitude of the increases in P n , T r and g s found in both our previous study by Guo et al [ 20 ] and the present study was similar to reported results concerning winter wheat from studies by Khamssi et al [ 46 ], Sun et al [ 47 ] and Zhang et al [ 48 ], reflecting the beneficial effects of SI in these photosynthetic parameters. Some studies have reported that enhancing P n and g s , particularly at the mid and later stages of grain filling, has significant effects on improving grain yield of crops, such as winter wheat, maize, rice [ 19 , 49 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…We propose that these combined factors are responsible for RIL2219’s inherent greater capacity for carbon assimilation and thus the ability to maintain higher yield stability than either parent under drought in the field, as supported by datasets from a large number of field trials under various drought gradients (unpublished observations). Evidence exists that wheat breeders have inadvertently selected for higher stomatal conductance in their quest for greater yield potential under optimal conditions, and this has also proved to be beneficial under water-limiting Mediterranean environments [67] , [64] , [68] , [69] , [70] , [65] , [71] , [72] , [73] , [74] . There was also evidence for greater osmotic adjustment ability in the two drought resistant lines Cham1 and RIL 2219 than in Lahn.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, leaf chlorophyll content (as a proxy of leaf photosynthesis) and stomatal conductance were proposed as proper criteria for identifying drought-tolerant genotypes under field conditions [16]. ese tow traits allow as well as the identification of germplasm combining improved water use efficiency and productivity under both well-watered or water-limited conditions [17].…”
Section: Introductionmentioning
confidence: 99%